2021
DOI: 10.1016/j.jstrokecerebrovasdis.2021.106084
|View full text |Cite
|
Sign up to set email alerts
|

An Association between Inflammation and Cerebral Venous Thrombosis: A Retrospective Study

Abstract: BackgroundEvidence is currently accumulating for the role of in ammation in cerebral venous thrombosis (CVT). Neutrophil/lymphocyte ratio (NLR), platelet/lymphocyte ratio (PLR), monocyte/high-density lipoprotein ratio (MHR), and systematic immune-in ammation index (SII) are easily obtainable indicators of systemic in ammations. However, there were few studies on the relationship between them and CVT.Therefore, we aimed to evaluate the connection between the occurrence of CVT and the in ammatory markers describ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 36 publications
0
22
0
Order By: Relevance
“…The pre-developed search strategy identified 2,664 records from PubMed, Embase, Web of Science, Cochrane library, and CINAHL databases. Based on the inclusion and exclusion criteria, a total of 13 studies were eligible for analysis ( 28 40 ). The flow diagram of the study selection process and exclusion reasons after full-reading are depicted in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The pre-developed search strategy identified 2,664 records from PubMed, Embase, Web of Science, Cochrane library, and CINAHL databases. Based on the inclusion and exclusion criteria, a total of 13 studies were eligible for analysis ( 28 40 ). The flow diagram of the study selection process and exclusion reasons after full-reading are depicted in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Of the 152,996 participants, 102,822 were male and the mean/median age ranged from 33 to 70 years. The published studies were conducted in four regions: China ( 28 , 29 , 31 , 32 , 34 , 35 , 39 , 40 ), Turkey ( 30 , 33 , 38 ), Poland ( 36 ), and United States ( 37 ). The determination of SII cutoff values was based on ROC analysis, Youden index, and quartiles.…”
Section: Resultsmentioning
confidence: 99%
“…SII is an independent prognostic factor for patients with non-chronic CVT, with high SII values on admission suggesting poor outcomes (75,77). Moreover, SII and NLR were positively correlated with CVT severity (74).…”
Section: Thrombo-inflammatory Biomarkersmentioning
confidence: 94%
“…Single-center clinical studies have reported significantly higher levels of PLR (74) and NLR (17,42,74) in patients with acute CVT than in patients with chronic CVT. Notably, the NLR (16,17,74) and PLR levels (74) are positively correlated with the baseline disability degree, with NLR being more commonly used to predict adverse outcomes in patients with severe CVT. Numerous studies have demonstrated that increased NLR levels are associated with poor prognosis in patients with CVT.…”
Section: Thrombo-inflammatory Biomarkersmentioning
confidence: 99%
See 1 more Smart Citation